La densité des mots dans Bouvard et Pécuchet - Norioki Sugaya (Flaubert: Revue Critique et Génétique)
How should we read a text as dense as Bouvard et Pécuchet? In the wake of many Flaubertian genetic studies, we will try once again to ponder the meaning of this encyclopedic novel’s textual opacity which reflects both its own genesis and the cultural context of that period. Our analysis focuses on two examples from chapter 3, on medicine, and aims to interpret the textual space of Bouvard as a site of memories (in the plural).